Complete analytical model of GaN MESFETs for high power and Microwave frequency applications - Shanta, Aysha Siddique; Huq, Tasneem Rumman; Hossain, Daraksha Binte; Mahmood, Riaz (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.